Skill Development: An Empirical Case Study in Nepal Bank Limited - Shrestha, Rohit Kumar (Scientific Researches in Academia, 2023)
What the state of skill development and in what ways the skill development is related to employee effectiveness at Nepal Bank Limited in Nepal are the research issues in this study. The study’s objectives are to determine existing skill development (SD) status and evaluate the relationship between SD and employee effectiveness. This research applied a descriptive and quantitative research design. Primary data have been collected through structured questionnaires. There are 21 commercial banks in Nepal. Nepal Bank Limited was selected as a sample unit based on the lottery technique. A total of 50 respondents were sampled by applying the purposive sampling method. Descriptive statistics were adopted to determine the existing state of skill development and employee effectiveness. The Likert Five-Point Scale was used as an instrument for answering perceptual questionnaire statements. In descriptive statistics, mean values of more than 3.44, and the remaining of them are nearest to 4. No statement has been less than the average value. Furthermore, the minority of the mean values of the statements in this table is more than 4, and the majority of the mean values are nearer to 4. Thus, it can be concluded that employees seem to agree that employee skill development and effective of them are sound. Similarly, the perception of the great majority of employees in almost all questionnaire statements is in favor of an agreement with these statements. Therefore, the conclusion can be drawn that the development of the skill of employees strongly related to employee effectiveness in the Nepal Bank Limited.